Multifactorial analysis of diarrhea in children: Economic, environmental, and behavioral perspectives - Triastuti, N Juni; Euclida Qolbun Rahman; Erna Herawati (Public Health Risk Assesment Journal, 2025)
Background: Diarrhea is a common illness among children, particularly in areas with inadequate environmental sanitation. This study seeks to examine the impact of economic status, environmental sanitation conditions, and defecation habits on the occurrence of diarrhea in children aged 5 to 11 years. Methods: The study employs an analytical observational design with a cross-sectional approach and includes 96 participants selected through purposive sampling. Data were analyzed using univariate methods, bivariate analysis with the Chi-Square test, and multivariate analysis with logistic regression. Findings: The findings revealed (1) a significant association between economic status and diarrhea incidence (p = 0.001); (2) a significant link between environmental sanitation and diarrhea cases (p = 0.000); (3) a notable relationship between defecation behavior and diarrhea incidence (p = 0.003); and a multivariate analysis confirmed a significant relationship between economic status, environmental sanitation, and defecation patterns with a p-value of 0.036. Conclusion: The goal is to gain deeper insights into the contributing factors of diarrhea and to support prevention and treatment strategies through economic development, sanitation awareness, and the promotion of healthy living. Novelty/Originality of this Article: This study offers an integrative analysis of economic, environmental, and behavioral factors affecting diarrhea in children, providing data-driven evidence to inform multifaceted public health interventions in sanitation-deficient areas.